Research and Evaluation for Passive Safety System in Low Pressure Reactor - Peng Chuanxin; Zhuo Wenbin; Chen Bingde; Nie Changhua; Huang Yanping (Science and Technology of Nuclear Installations)
Low pressure reactor is a small size advanced reactor with power of 180 MWt, which is under development at Nuclear Power Institute of China. In order to assess the ability and feasibility of passive safety system, several tests have been implemented on the passive safety system (PSS) test facility. During the LOCA and SBO accident, the adequate core cooling is provided by the performance of passive safety system. In addition the best-estimate thermal hydraulic code, CATHARE V2.1, has been assessed against cold leg LOCA test. The calculation results show that CATHARE is in a satisfactory agreement with the test for the steady state and transient test.